TINJAUAN EKONOMI SYARIAH TERHADAP PELAYANAN NASABAH PRIORITY BANK SYARIAH MANDIRI CABANG LHOKSEUMAWE - Hidayatina Hidayatina; Mutia Siska (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
The basic problem is the implementation of ordinary customer service to priority customers who seem to discriminate between one customer and another customer. The purpose of the research is to find out the implementation of priority customer service at PT. Bank Syariah Mandiri Lhokseumawe Branch and to find out how Islamic economic reviews on priority customer service. This type of research is field research, while the research approach is descriptive qualitative research is research that focuses on words rather than numbers. The sharia economic review of the Priority Customer Service is permitted, because of the hadith of the Prophet Muhammad. BSM also applies sharia economic principles, namely: monotheism, justice, trust and help. But the principle of justice they hold is to place rights in accordance with what has been mandated, namely priority customer rights that have been promised by the bank at the beginning of the agreement.